PR-Message Analysis as a New Method for the Quantitative and Qualitative Communication Campaign Study - Zakharchenko, Artem (Information & Media, 2022)
Communication practitioners often seek fast quantitative and qualitative analysis of the information campaign outcomes in the media space. Such analysis is required by PR departments of commercial brands, by political technologists, and by experts in information wars and ideology.A new approach for the analysis of information campaign outcomes is introduced in this paper. Using PR messages as a category for analysis of media coverage of information campaigns provides a framework for credible efficiency evaluation, as well as for the deep analysis of the factors contributing to achievements or failures. This method allows the campaign organizers to understand what message it is better to disseminate in the media. In other words, through the messages of what kind the opinion of the campaign initiator or their opponents is conveyed to the media audience more effectively.We consider a message to be a judgment in which an object or predicate relates to the substance of the information campaign. Using it as a category for analysis and several types of the message as subcategories of analysis allows us to combine qualitative and quantitative approaches and, at the same time, avoid many restrictions of content analysis, discourse analysis, and narrative analysis.We show how the method works on the example of the failed information campaign that promoted a lobbyist and populist bill in the Ukrainian parliament. We showed that only our method could explain the reasons for its failure and provide the best way to improve the communication.
Keywords: information campaigns; content analysis; discourse analysis; PR message; information attack